Applications of 3D printing and digital transformation in aerospace engineering and telecommunication technologies - Ivanova, Yoana (Yearbook Telecommunications, 2024)
The aim of the development is to present the overall process of building functional prototypes for the purposes of aerospace engineering and telecommunication technologies, based on specific examples from the author's scientific and practical work. The scientific-applied contribution of the research is expressed in the correct selection and comparative analysis of compatible software products and devices for 3D modeling, digital transformation and 3D printing of objects from the space infrastructure and. in particular, of radio technical devices as key components of telecommunication satellites. The presented practical results are in the form of a final product that, if the criteria for precise modeling and the selection of a suitable material for 3D printing are met, can satisfy the quality criteria of the relevant industry for which it is intended.